Environmental Equity and Spatiotemporal Patterns of Urban Tree Canopy in Atlanta. (March 2023) - Koo, Bon Woo; Boyd, Nico; Botchwey, Nisha; Guhathakurta, Subhrajit
While previous studies in environmental equity found positive relationships between tree canopy and socioeconomic/demographic status of neighborhoods, few examined how changes in tree canopy are associated with changes in socioeconomic/demographic status. This study confirms that the relationship between them in Atlanta is changing and the hypothesis of inequitable distribution of tree canopy concerning demographic attributes cannot be fully supported beyond 2000. In addition, the proportion of African Americans can have different effects on the estimated tree canopy as poverty rates vary. Planning to mitigate environmental inequities through tree plantings requires more careful analysis that goes beyond the socioeconomic/demographic attributes of the population.